Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyńThe role of statins in therapy of heart failure - Rozentryt, Piotr; Nowak, Jolanta; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
In patients with heart failure increased level of cholesterol is accompanied by lower mortality. It has not as yet been determined whether low concentration of cholesterol is a marker or a mediator of more advanced heart failure. This paradox, referred to as reversed epidemiology, calls for cautiousness in hypolipemic treatment of this group of patients. Among the drugs used, the leading role is played by statins. The lowering of cholesterol concentration is the most noticeable action of these drugs. This work discusses statin mechanics with particular emphasis on those which may have beneficial effects on pathophysiological processes leading to heart failure. Epidemiological data documenting the importance of statins in heart failure prevention and in lowering the mortality rate in patients with heart failure are also quoted.